Livestock management and automation system using radio waves - Aris, Ishak; Tengku Muda Mohamed, Mahmud; Khoshgoftar Ziabari, Seyedeh Saeedeh; Hassan, Azmi; Mohd Sharif, Shaibi (2012)
The present invention provides a multiband radio frequency identification-based embedded system for livestock management and automation system, in which an animal carriers a passive radio frequency identification (RFID) tag. The system comprises an automation means that is adopted to control and monitor equipments in a house of the tagged animal; an animal detection means to identify and monitor animals when entering the RFID coverage range; a server to save data of the animals received from the animal detection means and automation system; and an internet connection to send the data to the user.